A new species of Vetanthocoridae (Heteroptera: Cimicomorpha) from the Lower Cretaceous of China. (September 2016) - Tang, Di; Yao, Yunzhi; Ren, Dong
Abstract: A new species, Crassicerus limpiduspterus sp. n., is characterized, described and assigned to the tribe Crassicerini of the fossil family Vetanthocoridae. All of the specimens were collected from the Lower Cretaceous Yixian Formation at Chaomidian Village, Liaoning Province. The Crassicerini are interpreted to have thrived in live plant habitats, including flowers, shrubs and trees, based on their antennal type.